Blue Orchard Bee, Osmia lignaria Say (Insecta: Hymenoptera: Megachilidae) - Alden Estep; Catherine Zettel-Nalen; James Ellis (EDIS)
The blue orchard bee, Osmia lignaria Say (Fig. 1), is a solitary mason bee native to the west coast of the United States and Canada. It is of great interest for use as a native pollinator of fruit trees and blueberries, and is easily managed due to its favorable biological characteristics. Blue orchard bees can be purchased online for pollination, and they are shipped as pupae ready to emerge in the spring. This 4-page fact sheet was written by Alden Estep, Catherine Zettel-Nalen, and James Ellis, and published by the UF Department of Entomology and Nematology, March 2013.